Answer:
the rate of change of the angle is -767/100 rad/s
Explanation:
Assuming that the string is released at the origin (0,0) from rest , then the length of the string is:
y = 1/2*g*t²
x= v*t
then
L = √(x²+y²) = √[(1/2*g*t²)²+(v*t)²]
when L=200 m
L²= (1/2*g)²* t⁴ + v² * t²
for L= 200 m
doing z=t²
(1/2*g)²* z² + v² * z - L² = 0
(1/2 * 32.174 ft/s²) * z² + (50 ft/t)² * z - (200ft )² = 0
16.087 ft/s² * z² + 2500 ft²/s² * z - 40000 ft² = 0
z = 14.62 s²
t = √z = √(14.62 s²) = 3.82 s
since
tg θ =(H-y)/x = H/(v*t) - g/(2*v) * t
θ = tan⁻¹ (H/(v*t) - g/(2*v) * t)
since the rate of change equals the derivative with respect to the time
dθ/dt = (-1)/[1+ (g/(2*v) * t)²] * [- H/(v*t²) - g/(2*v) ]
dθ/dt = [-k - H/(v*t²) ]/[1+ [H/(v*t) - k*t]²] , k= g/(2*v)
since k= g/(2*v) = 32.174 ft/s²/( 2*50 ft/s) = 0.32174 s⁻¹ , t= 3.82 s
dθ/dt = [-k - H/(v*t²) ]/[1+ [H/(v*t) - k*t]²] = -[0.32174 s⁻¹ + 400 ft/(50 ft/s*3.82 s)] / [ 1+ (400 ft/(50ft/s*3.82 s) - 0.32174 s⁻¹ * 3.82 s )²]
dθ/dt = -7.67 s⁻¹ = - 767/100 rad/s